Phosphorus fertilization of corn using subsurface drip irrigation - Olson, Jeremy Ray (Kansas State University, 2011)
In recent years, subsurface drip irrigation (SDI) acres have increased substantially. The use of SDI on corn (Zea Mays L.) in the Great Plains has increased due to increased land costs, reduced irrigation water availability, and higher commodity prices. Applying phosphorus (P) fertilizer through a SDI system becomes a major advantage, but further investigation of the interaction between water and fertilizer is needed. Sub-surface drip irrigation systems can be used to better improve the application efficiencies of fertilizers, applying in wet soil-root zones can lead to better uptake of soil applied materials. The objectives of this study were to determine how corn responds to P fertilizer applied via SDI and to create methodologies to simulate fertilizer and irrigation water compatibility tests for use in SDI systems. A plot sized SDI system was installed near Manhattan, KS to evaluate P treatments. Eight separate P fertilizers were applied via SDI mid-season at a rate of 34 kg P2O5 ha-1 and split-plots were created with 2x2 starter band at planting. Nitrogen was a non-limiting factor, with 180 kg N ha-1 applied as urea. Both starter fertilizer and injected fertilizer affected corn grain yield as indicated by the starter by treatment interaction. Split applying starter fertilizer at planting increased yield. A secondary laboratory study was conducted to evaluate the water and fertilizer interactions. A filtration system was used to simulate field conditions and each fertilizer/water mix was filtered through a 400 mesh filter paper to evaluate fertilizer precipitant formation. Sixteen common fertilizers were analyzed with different rates of Avail. Differences were observed between fertilizer treatments, visually and quantitatively. A secondary P soil movement field study was performed to quantify P concentrations around the SDI emitter. Soils were sampled in a 30.5 cm by 30.5 cm square adjacent to the emitter on a control treatment and a fertilized treatment, in both years of the study. Visual and quantitative differences were observed between the two treatments in both years of the study. When P fertilizers were added to the SDI system, higher P concentrations were found very close to the emitter orifice. Control treatments exhibited lower P concentrations around the emitter than fertilized treatments.
Keywords: Corn; Fertilization; Phosphorus; Subsurface Drip Irrigation; Agriculture, General (0473); Agronomy (0285)